Effectiveness and Practicality of eKTANG as a Digital Treatment for Diabetes and Relevant Influence Factors - Xiaohua Lu; Dalong Guo; Lie Feng; Yan Zhou; Chuangbiao Zhang; Jiaying Li; Yin Jiang (Tehran University of Medical Sciences, 2022)
Background: This work explored the effect of eKTANG, a new healthcare mode for diabetes patients, on diabetes management. Methods: Allowing general utilization of medical service and health management based on Internet, eKTANG obtained the precise data like blood glucose and blood pressure examined by an intelligent glucometer, from which doctors and the nursing team will promptly analyze the data and return feedback to the patients. In our study, overall 204 patients receiving eKTANG management over 3 months in First Affiliated Hospital of Jinan University from May 2019 to Aug 2020 were enrolled as the research objects, with data collected from patient records. Results: Through the biochemical test on relevant indexes of blood glucose, it was observed that FBG, PBG, HbA1c, TG, TC, LDL levels after management were lower than before whereas HDL expression after were lower than before. Contrasted with substandard group, standard group performed younger age, lower proportion of the married, decreased proportion of microvascular and macrovascular complications, longer course of disease, more frequent glucose monitoring, declined time of hyperglycemia and time of alarms, elevated time of euglycemia, increased proportion of diet control, more amount of exercise and higher compliance, as the number of patients choosing oral medicine in standard group was more than substandard group. The course of disease and time of hyperglycemia were risk factors of HbA1c standard reaching whereas frequency of glucose monitoring (≥1 time/week) and time of euglycemia were protective factors. Conclusion: eKTANG effectively improved diabetes management.